Lexical Borrowing in Malaysian English: Influences of Malay - Siew Imm Tan (Lexis: Journal in English Lexicology)
During its evolution in the region that is today Malaysia, English has come into contact with a range of diverse, typologically-distinct languages. All these languages have influenced the lexicon of Malaysia English (ME), but it is Malay that has contributed to some of the most remarkable characteristics of this variety of English (see, for example, Lowenberg [1986 and 2000]; and Morais [2001]). This paper explores how the English-Malay contact has resulted in the incorporation of Malay features into the lexicon of ME. Using a corpus-based approach, the study analysed a comprehensive range of borrowed features extracted from the author’s Malaysian English Newspaper Corpus (MEN Corpus) for the linguistic processes behind the borrowing phenomenon. Haugen’s [1950] groundbreaking work on lexical borrowing provides the theoretical framework of this study. It is proposed that the underlying systematicity of the processes involved is reflected in the linguistic outcomes, and that there is much potential for corpus-based lexicography where ME is concerned. To highlight the non-arbitrariness of the borrowing phenomenon, the social and linguistic factors that motivate ME users to incorporate Malay lexical features into their variety of English are examined.